Identification of specific nucleotide sequences and structural elements required for intronic U14 snoRNA processing. - Xia, L (1997)
Vertebrate U14 snoRNAs are encoded within hsc70 pre-mRNA introns and U14 biosynthesis occurs via an intron-processing pathway. We have shown previously that essential processing signals are located in the termini of the mature U14 molecule and replacement of included boxes C or D with oligo C disrupts snoRNA synthesis. The experiments detailed here now define the specific nucleotide sequences and structures of the U14 termini that are essential for intronic snoRNA processing. Mutagenesis studies demonstrated that a 5', 3'-terminal stem of at least three contiguous base pairs is required. A specific helix sequence is not necessary and this stem may be extended to as many as 15 base pairs without affecting U14 processing. The spatial positioning of boxes C and D with respect to the terminal stem is also important. Detailed analysis of boxes C and D revealed that both consensus sequences possess essential nucleotides. Some, but not all, of these critical nucleotides correspond to those required for the stable accumulation of nonintronic yeast U14 snoRNA. The presence of box C and D consensus sequences flanking a terminal stem in many snoRNA species indicates the importance of this "terminal core motif" for snoRNA processing.